DIGITAL TRANSFORMATION OF THE EDUCATION SYSTEM. FROM ADAPTABILITY TO PERFORMANCE - ONETIU DANIEL DARIUS; GLOVAŢCHI BOGDANA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2020)
n this paper we addressed the impact of digital transformation on the university education system, but also its adaptability and that of organizations to digitalization. I tried to highlight the process of adaptability as a result of the performance of an institution or an organization. Given the fact that the online presence of an educational institution is a main point of contact with its target groups and its main stakeholders. Whether we are talking about social media, internet or website. At the moment the world is based on information coming from web 2.0 platforms, therefore the adaptability of institutes to digital transformation plays a very important role in the formation and communication of its main target groups (in the case of this paper being students). This research begins with a detailed presentation of the literature focusing on: digital transformation, social media marketing, analytical social media and the use of OSH by university education. We continue with the elaboration of a case study assigned to 61 respondents(61 students of the West University of Timisoara) regarding the use of social networks. Then their answers are interpreted, and at the end I drew conclusions about the impact of digital transformation on the education system, adaptability to innovation systems, but I also made a comparison between the adoption of new technologies by educational institutions and organizations. . Another important topic that this paper touches on is the importance of creating a marketing department within an institution or organization and how it can influence performance.